A global geography of synchrony for terrestrial vegetation. Issue 8 (29th May 2017) - Defriez, Emma J.; Reuman, Daniel C.
Abstract: Aim: Previous work demonstrated a pronounced geography of synchrony for marine phytoplankton and used that geography to infer statistical environmental determinants of synchrony. Here, we determine whether terrestrial vegetation (measured by the enhanced vegetation index, EVI) also shows a geography of synchrony and we infer determinants of EVI synchrony. As vegetation is the basis of the terrestrial food web, changes in spatio‐temporal vegetation dynamics may have major consequences. Location: The land. Time period: 2001–2014. Major taxa: Plants. Methods: Synchrony in terrestrial vegetation is mapped globally. Spatial statistics and model selection are used to identify main statistical determinants of synchrony and of geographical patterns in synchrony. Results: The first main result is that there is a pronounced and previously unrecognized geography of synchrony for terrestrial vegetation. Some areas, such as the Sahara and Southern Africa, exhibited nearly perfect synchrony, whereas other areas, such as the Pacific coast of South America, showed very little synchrony. Spatial modelling provided the second main result, namely that synchrony in temperature and precipitation were major determinants of synchrony in EVI, supporting the presence of dual global Moran effects. These effects depended on the time‐scales on which synchrony was assessed, providing our third main result, namely that synchrony of EVI and its geography are time‐scale specific. Main conclusions: To our knowledge, this study is the first to document the geography of synchrony in terrestrial vegetation. We showed that geographical variation in synchrony is pronounced. We used geographical patterns to identify determinants of synchrony. This study is one of very few studies to demonstrate two separate synchronous environmental variables driving synchrony simultaneously. The geography of synchrony is apparently a major phenomenon that has been little explored.